Pengaruh Model Pembelajaran Snowball Throwing Terhadap Minat Belajar Siswa Subtema Materi Pahlawan Indonesia Muatan Ilmu Pengetahuan Sosial di Kelas IV SD Negeri 3 Lando - Meri Yuliani; Muhamad Ridwan Habibi; Sahara Nandasari (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This study aims to determine the increase in learning interest in social studies with the theme of Indonesian Heroes in grade IV at SDN 3 Londo East Lombok in the 2022/2023 academic year after implementing the Snowball Throwing learning model. This type of research is classroom action research (PTK) with the research subjects being Class IV students, totaling 36 students. The background of this research is the low interest in learning in class IV students of Class 3 at SDN 3 Londo. The low interest in student learning is caused by the teacher's inaccuracy in choosing a learning model resulting in low student interest in learning. To improve the quality of learning is to vary the learning model, one of which is through the Snowball Throwing model. This research is classroom action research carried out in two cycles and each cycle consists of 4 stages of activity namely planning, action, observation and reflection. The research subjects were 34 class 3 students at SDN 3 Londo. The research instrument used observation sheets and field notes. The results of research on students' learning interest in social studies learning with the theme of Indonesian heroes with the percentage formula P=(F/N)x100%. The results showed that there was an increase in students' interest in learning by applying the Snowball Throwing model